WHAT DRIVES PEOPLE'S INTEREST IN SHARIA INSURANCE? EVIDENCE FROM PALANGKA RAYA - Umi Purwaningsih; Putri Nurmala; Muhammad Riza Hafizi (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2021)
This studi aims to analyze factors affecting people become member of sharia insurance in Palangka Raya, Central Borneo, Indonesia. This research approach uses a quantitative approach. The variables used in this study, product, price, promotion, lifestyle and economic conditions. The method used in data collection using purposive sampling method, by distributing online questionnaires. The number of samples in this study were 42 respondents. The analytical tool used to determine the public's interest in participating in Prudential sharia insurance in Palangka Raya City is to use SPSS 23. The results of this study indicate that there is a significant positive effect on promotion and lifestyle variables on interest in Prudential sharia insurance, this is evidenced by the F test, which shows a significance level of 0.000. This is because the magnitude of the significance level of the F test from the F count value of 16,215 with the F table value of 2.5, this indicates that the F count value is greater than the F table value (16, 215 > 2.5). In this study, the magnitude of the influence of the Adjusted R Square of the promotion and lifestyle variables is 0,650 or 65% which affecting become sharia insurance participant in Palangka Raya. Meanwhile, based on the results of the T test, it shows that the variables of product, price and economic conditions are not significant. This is because the Palangka Raya is not as big as the cities in the capital, so people who use the services of Sharia Insurance are still not priority for the people of Palangka Raya. This study contributes empirically to the describe sharia insurance in Palangka Raya. In addition, the existing sharia insurance in the Palangka Raya should be re-socialized so that people are more familiar and using sharia insurance services compared to using conventional insurance. Islamic insurance uses the concept of protecting each other. This concept is different from conventional insurance, where participants pay premiums to insurance companies.